Draft Genome Sequence of Bordetella trematum Strain HR18 - Chang, Dong-Ho (Genome Announc, 2015)
The genus Bordetella is reportedly a human or animal pathogen and environmental microbe. We report the draft genome sequence of Bordetella trematum strain HR18, which was isolated from the rumen of Korean native cattle (Hanwoo; Bos taurus coreanae). It is the first genome sequence of a Bordetella sp. isolated from the rumen of cattle.